Shipping and Trading Activities of Butonese in the Archipelago During the 17th and 18th Centuries: Patterns, Networks, and Commodities - La Malihu (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This article analyzes the shipping and trading activities of the Butonese in the Archipelago in 17th and 18th centuries with the main focus on patterns, networks and commodities. Using the historical method which consists of four stages, namely: heuristics, criticism, interpretation and historiography. The results of the analysis show that Butonese is one of the maritime ethnic groups that is quite active in shipping and trading activities in the archipelago. It is also thick with maritime nuances which is characterized by its geographical environment consisting of islands and is also marked by the use of the boat metaphor to describe the existence of their kingdom. The shipping pattern follows the monsoon wind pattern which is parallel to the types of commodities traded between the West and East Regions which are symbiotic in nature. The shipping network covers eastern regions of the archipelago such as Maluku, Nusa Tenggara and Sulawesi, as well as western areas such as Java, Sumatra and Singapore. Meanwhile, the commodities traded include spices, marine products, agricultural and forest products as well as handicrafts such as clothing, household utensils, weapons, and most importantly slaves. The main challenge faced by Buton was the intervention of various external forces who wanted to exert influence in Buton such as the VOC, Gowa, and Ternate in order to control shipping and trading routes between the West and East Regions. Another disturbance is the intensive pirate power operating in line with the development of shipping and trading activities in the sea waters of Buton.